Kiedy koniec wieńczy dzieło. Skuteczne zdziwienie „w teatrze życia codziennego” - Monika Wiśniewska-Kin (Problemy Wczesnej Edukacji)
The article presents the results of research carried out under the Innovation Incubator 2.0 project in the 2018/2019 school year in a selected kindergarten, in a metropolitan environment (Łódź). All the project activities involved the implementation of three areas: first, constructing the program assumptions of the ‘Two Languages – One Way’ project and analyzing the educational market, and second, developing a cultural ‘toolkit’ (Bruner 2006: 35) in the form of demonstration charts and methodological aids, thirdly, testing the final product “Two Languages – One Way” by the teacher of glottodidactics. The research adopted a strategy for a didactic intervention. The researcher acted as an observer as a participant, and the material came from participant observation. The observation focused on interventions initiated according to their design. The observation covered student activities, as well as the effects of these activities. Research results reconstructed children’s skills in identifying sounds and letters as well as reading by slipping from sound to sound.